Auditoría de Gestión al Gobierno Autónomo Descentralizado Parroquial Rural de Cumbaratza del Cantón Zamora, durante el Periodo 01 de enero Al 31 de diciembre del 2015 - Benítez Alulima, Sonia Marlene (2018)
The present titration work, "AUDIT OF MANAGEMENT TO THE AUTONOMOUS, DECENTRALIZED RURAL PARISH OF CUMBARATZA DEL CANTÓN ZAMORA, DURING THE PERIOD JANUARY 1 TO DECEMBER 31, 2015", has as main purpose the fulfillment of the following general objective: To carry out the Audit of Management to the Autonomous Decentralized Parochial Rural Government of Cumbaratza of the Zamora Canton, during the period January 01 to December 31 of 2015, for its development the specific objectives were directed to: Evaluate the Internal Control System, that for its fulfillment was applied the internal control questionnaire, which helped to know the level of risk and the level of confidence of each area examined; The second objective was addressed to the application of Management Indicators that allow to measure the efficiency and effectiveness in the fulfillment of the objectives, plans, and programs, through the application of indicators of the annual operating plan to measure the efficiency and effectiveness of the proposed activities. . The third objective was to prepare the Audit report which was made based on the result of the performance of the management audit to the Autonomous Decentralized Parish Government of Cumbaratza, which contains comments, conclusions and recommendations that will allow its directors to take corrective measures 5 for the improvement of management and in this way contribute to the development of the entity. As a result of the management audit of the Autonomous Decentralized Parochial Rural Government of Cumbaratza, it is established that the internal regulation must be updated so that the institutional management has an administrative support for its normal development, a manual of functions must be prepared that allows them to know the functions of each server, evaluate the performance of the staff to improve the quality of the service and the achievement of the objectives, create a web page that allows to publish the information to the citizenship, and with regard to the Annual Operating Plan were not reached In its entirety, the proposed goals are due to lack of budget, so we must perform the appropriate processes to obtain the necessary resources to meet the goals established in it.